Demokrati versus repræsentation:: Sociale bevægelser og teorien om ’imperativmandatet’ i Den Franske Revolution - Eggers, Nicolai von (Slagmark - Tidsskrift for idéhistorie, 2015)
This article investigates the theory of an imperative mandate as presented in the radical French revolutionary Jean-François Varlet’s text Project for a Special and Imperative Mandate from 1792. This text is taken as, and shown to be, representative for a widespread understanding of radical democracy during the French Revolution in which deputies were not understood as ‘representatives’ but as ‘mandataries’ who were legally bound to follow the instructions of their commettants. As an essential part of this radical conception of democracy, social movements were to be constantly mobilized and able to supervise the political system. This entails a shift in the balance of power from the state to the social movements, and as such it expresses a different conception of democracy than that of liberal democracy with its rule of law and state monopoly of violence.